EXCESSIVE SCREEN USE: PREVALENCE AND RISKS ASSOCIATED WITH CHILD DEVELOPMENT (International Seven Journal of Health Research, 2025)
The present study aimed to identify the consequences of excessive screen use in children, as well as to evaluate social interaction, measure Body Mass Index (BMI), and conduct a standard ophthalmological test using the Snellen Chart with 5th-grade elementary school students at CEM Prof. Valdir Gonçalves de Lima, in the municipality of Votuporanga, São Paulo, Brazil. The study is characterized as exploratory with a quantitative–qualitative approach, using questionnaires and interactive activities to foster bonding between the participants and the medical students.